Effects of Dimerization, Dendrimerization, and Chirality in p-BthTX-I Peptide Analogs on the Antibacterial Activity and Enzymatic Inhibition of the SARS-CoV-2 PLpro Protein - Bitencourt, Natália Vitória [UNESP] (2023)
Recent studies have shown that the peptide [des-Cys11,Lys12,Lys13-(p-BthTX-I)2K] (p-Bth) is a p-BthTX-I analog that shows enhanced antimicrobial activity, stability and hemolytic activity, and is easy to obtain compared to the wild-type sequence. This molecule also inhibits SARS-CoV-2 viral infection in Vero cells, acting on SARS-CoV-2 PLpro enzymatic activity. Thus, the present study aimed to assess the effects of structural modifications to p-Bth, such as dimerization, dendrimerization and chirality, on the antibacterial activity and inhibitory properties of PLpro. The results showed that the dimerization or dendrimerization of p-Bth was essential for antibacterial activity, as the monomeric structure led to a total loss of, or significant reduction in, bacterial activities. The dimers and tetramers obtained using branched lysine proved to be prominent compounds with antibacterial activity against Gram-positive and Gram-negative bacteria. In addition, hemolysis rates were below 10% at the corresponding concentrations. Conversely, the inhibitory activity of the PLpro of SARS-CoV-2 was similar in the monomeric, dimeric and tetrameric forms of p-Bth. Our findings indicate the importance of the dimerization and dendrimerization of this important class of antimicrobial peptides, which shows great potential for antimicrobial and antiviral drug-discovery campaigns.